Spatial prediction of dynamic interactions in rats - Tereza Dvorakova; Veronika Lobellova; Paloma Manubens; Abel Sanchez-Jimenez; Jose Antonio Villacorta-Atienza; Ales Stuchlik; David Levcik (PLoS ONE, 2025)
Animals and humans receive the most critical information from parts of the environment that are immediately inaccessible and highly dynamic. The brain must effectively process potential interactions between elements in such an environment to make appropriate decisions in critical situations. We trained male Long-Evans rats to discriminate static and dynamic spatial stimuli and to generalize novel dynamic spatial stimuli displayed on an inaccessible computer screen. We provide behavioral evidence indicating that rats encode dynamic visuospatial situations by constructing internal static representations that capture meaningful future interactions between objects. These observations support previous findings in humans that such internal static representations can encapsulate relevant spatiotemporal information of dynamic environments. This mechanism would allow animals and humans to process complex time-changing situations neatly.